Analysis of the full-length VP2 protein of canine parvoviruses circulating in Hungary - Cságola, Attila; Varga, Szilvia; Lőrincz, Márta; Tuboly, Tamás (Archives of virology, 2014)
In recent years, the number of cases of disease caused by canine parvovirus 2 (CPV-2) in vaccinated dogs has increased. The aim of the present study was to identify CPV-2 strains present in Hungary. Forty-two out of 50 faecal specimens examined were positive, and 25 VP2 sequences were determined and analysed. Based on the current classification, the Hungarian viruses belong to New CPV-2a type, except two viruses that are recombinants of vaccine viruses and CPV-2a strains. The Tyr324Ile alteration was detected for the first time in Europe, and a “Hungarian-specific” substitution (Ala516Thr) was also identified in this study. The immunologically important parts of the currently spreading canine parvoviruses were examined and found to differ greatly from the vaccine strains that are widely used in Hungary.